Analisis Pertumbuhan Zakat Pada Aplikasi Zakat Online Dompet Dhuafa - Andi Hidayat; Mukhlisin Mukhlisin (ITB AAS INDONESIA Surakarta, 2020)
Technological developments are now penetrating the world of worship, for those who want to pay zakat even easier. A number of online applications including online shopping provide zakat payment features for muzakki. Looking at the data in the National Zakat Agency that the potential for zakat in 2019, based on the IIPZ association and Indonesia's zakat outlook, the potential for zakat is around Rp. 233.8 trillion divided into 5 objects of Zakat. In 2016 and 2017, zakat income was only around 6 trillion. The huge potential of zakat in Indonesia makes all zakat practitioners or zakat collection bodies have to find ways to maximize the potential for zakat and be able to create poverty in Indonesia. From efforts to manage zakat efficiently, Dompet Dhuafa as Amil zakat implements an online application system for zakat, the goal is to facilitate and improve zakat services for the better, with this online zakat application it is hoped that it will be able to absorb some of the existing potential zakat and help make it easier for people to pay zakat because limited distance and time.The purpose of this research in general is that the development and growth of zakat will increase with the existence of online zakat collection. In particular, to make it easier for muzakki in distributing zakat.This research uses qualitative research methods which are commonly referred to as naturalistic research methods because the research is carried out in natural conditions (natural setting), the research data sources are primary and secondary. The results and findings of the study are the growth of zakat from each year, either from the growth of zakat in the online zakat system or in the overall zakat income every year.